Theoretical and practical problems of implementing energy management at enterprises - Bezzubko, L.; Bezzubko, B. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2025)
The relevance of implementing energy management systems (EMS) is related to the rising cost of fuel and resource consumption, as well as the large-scale destruction of national energy supply facilities during the war. Taking into account the requirements of sustainable development, rational use of natural resources and increasing social responsibility in the process of recovery contribute to the formation of EMS at Ukrainian enterprises. The article is aimed at clarifying theoretical concepts, systematising the main problems and directions of their solution in the process of implementation of the energy management system at Ukrainian enterprise. The EMS should be considered as a part of the overall enterprise management system, which has a certain organisational structure, performs managerial functions, duties and powers, procedures, processes, and uses resources to ensure the formation, implementation and achievement of energy saving policy goals. The authors characterise EMS as: 1) technology: on the basis of which energy saving is carried out; 2) energy saving strategy, which is implemented at different levels of management; 3) as a process characterised by making managerial decisions that affect the achievement of the set goals. In the article, the authors define the main tasks, principles, and functions of this system. The EMS is related to quality management (based on ISO 9001) and environmental management. The authors have identified and systematised the directions of solving practical problems in the implementation of the EMS: 1) problems faced by the company's management and specialists of an enterprise due to misunderstanding of the essence of EMS; 2) absence of clearly defined economic mechanisms for ensuring energy saving and material interest in implementation of such measures; 3) absence of data collection systems at enterprises, significant cost of equipment for measuring energy consumption. To solve the identified problems, the article proposes targeted advanced training of managers and specialists in the field of energy saving and implementation of EMS; improvement of training of qualified energy managers.The article emphasises the need to increase the role of energy managers in modern conditions - professionally trained specialists who make managerial decisions and are responsible for energy saving at enterprises.